Structural basis of ligand recognition in 5-HT3 receptors - Thompson, Andrew J. (2013)
The 5-HT3 receptor is a pentameric serotonin-gated ion channel, which mediates rapid excitatory neurotransmission and is the target of a therapeutically important class of anti-emetic drugs, such as granisetron. We report crystal structures of a binding protein engineered to recognize the agonist serotonin and the antagonist granisetron with affinities comparable to the 5-HT3 receptor. In the serotonin-bound structure, we observe hydrophilic interactions with loop E-binding site residues, which might enable transitions to channel opening. In the granisetron-bound structure, we observe a critical cation–π interaction between the indazole moiety of the ligand and a cationic centre in loop D, which is uniquely present in the 5-HT3 receptor. We use a series of chemically tuned granisetron analogues to demonstrate the energetic contribution of this electrostatic interaction to high-affinity ligand binding in the human 5-HT3 receptor. Our study offers the first structural perspective on recognition of serotonin and antagonism by anti-emetics in the 5-HT3 receptor.